Transient high-energy flares from accreting black holes - Vieyro, Florencia Laura (2010)
We present a model for high-energy flares in accreting black holes based on the injection in a magnetized corona of a non-thermal population of relativistic particles. Coupled transport equations are solved for all species of particles and the electromagnetic and neutrino output is predicted for the case of Galactic black holes.